2020
DOI: 10.1016/j.psj.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Protease supplementation attenuates the intestinal health damage caused by low-protein diets in Pekin ducks

Abstract: The objective of this study was to investigate the effects of low-protein diets with low digestibility of feed ingredients on intestinal damage and to explore whether the protease supplementation can alleviate the damage in Pekin ducks. A total of 576 Pekin ducklings (6 replicate pens, 16 ducks/pen) were randomly assigned to 6 dietary treatments (3 × 2 factorial arrangement) in a randomized complete block design. Factors were CP levels (13.5%, 15.5%, and 17.5%) and protease (0 or 20,000U/kg). Compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
0
0
Order By: Relevance
“…However, in the present study, meeting AA requirements such as methionine, lysine, threonine, arginine, valine, isoleucine, and tryptophan on a low-protein diet resulted in linearly depressed growth performance (p<0.05), regardless of various protein sources. The lowering CP levels affected to reduce the growth performance, as also reported by Wang et al [27], the result was validated by the data, where reduction CP levels suppressed the FI, BW, weight gain, and ADG and increased FCR. Wang et al [28] in their research stated that a decrease in feed protein levels (13.5% and 15.5%) reduced FI and BW in ducks aged 15 to 35 days.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, in the present study, meeting AA requirements such as methionine, lysine, threonine, arginine, valine, isoleucine, and tryptophan on a low-protein diet resulted in linearly depressed growth performance (p<0.05), regardless of various protein sources. The lowering CP levels affected to reduce the growth performance, as also reported by Wang et al [27], the result was validated by the data, where reduction CP levels suppressed the FI, BW, weight gain, and ADG and increased FCR. Wang et al [28] in their research stated that a decrease in feed protein levels (13.5% and 15.5%) reduced FI and BW in ducks aged 15 to 35 days.…”
Section: Discussionsupporting
confidence: 83%
“…The supply of non-essential amino acids such as glycine, glutamine, and proline contributed to the development of intestinal villi [ 33 ]. In their study, Wang et al [ 27 ] discovered that a decrease in essential amino acids, particularly free branched chain amino acids, damaged intestinal morphology. This was supported by the findings of Facey et al [ 32 ], who discovered that low concentrations and digestibility of proteins had a negative impact on development and function of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the growth performance reached the control level (CP, 18.55%) when supplementing the major AA pattern and all AA patterns in the low-protein diets (CP, 15.55%) in the goslings. Similar results were observed in low-protein diets in chickens ( Bezerra et al, 2016 ; van Harn et al, 2019 ; Teng et al, 2021 ), laying hens ( Alagawany et al, 2020 ; Uyanga et al, 2022 ), ducks ( Xie et al, 2017 ; Jiang et al, 2018 ), quail chicks ( Elsayed et al, 2021 ), and goose ( Wang et al, 2020 ). It is concluded that the growth performance would not be adversely affected by low-protein diets when the appropriate amount of AA is supplemented.…”
Section: Discussionsupporting
confidence: 76%
“…The significant effect of dietary protease supplementation on meat color is noted in the present study where protease reduced redness and yellowness in minced breast meat at 35 days post-hatch. However, dietary protease supplementation has not influenced chicken meat color in previous studies (Xu et al, 2017;Lu et al, 2020;Sumanasekara et al, 2020;Wang et al, 2020). Higher meat pH value seems to be influential in generating darker or reddish color in meat (Fletcher, 1999;Wattanachant et al, 2004); however, it is not the case in the present study.…”
Section: Resultscontrasting
confidence: 60%